IDENTIFICATION OF POTENTIAL INVESTMENT COMMODITY FOOD CROPS POTENTIAL IN NORTH SUMATRA - Akbar habib; Risnawati ,; Desi Novita (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
The role or contribution of the agricultural sector still dominates the economy of North Sumatra are areas of excellence that should be scaled back. The purpose of this research is to menganilisis any commodity that becomes a commodity in the province of North Sumatra. The data used in this research is the primary data and secondary data. Primary data is data obtained directly from the source. Neither the facts nor analysis of data from multiple sources in the field. Secondary data is data obtained from the Central Statistics Agency (BPS) of North Sumatra and the database of the Ministry of Agriculture. The data used in this study are the data of commodity production of food crops in the five years of observations in the year 2010 - 2014. Based on the analysis of Location Quotient Overall commodity crops belonging seed is corn. A financial analysis of corn plants seen from the calculation B / C ratio of 1.26 or greater than 1. So we can conclude the analysis of the corn crop farming viable in North SumatraKeywords: potential of the region, agricultural commodity, Location Quetient, financial analysis